Effects of alcohol on attentional mechanisms involved in figure reversals. (7th August 2013) - O'Brien, Claire; Harris, Mike; Higgs, Suzanne
Abstract : Objective: The impairing effects of alcohol on attention are well documented and are thought to involve inhibitory mechanisms. We used ambiguous figures (Face‐Vase and Necker cube) to test whether the intentional control mechanism is more vulnerable to the effects of alcohol than the automatic mechanism. Method: Participants were assigned to an alcohol (Study 1, N  = 15; Study 2, N  = 18), placebo (Study 1, N  = 15; Study 2, N  = 20) or control (Study 1 only, N  = 10) group. The doses of alcohol were 0.8 g/kg for men and 0.75 g/kg for women. Participants were shown the Face‐Vase and Necker cube figures and two variants of each, which were biased in varying degrees towards one interpretation. Study 1 assessed the automatic control mechanism by asking participants to report spontaneous reversals. Study 2 assessed the intentional control mechanism by asking participants to increase reversal rate. Results: In Study 1, reversal rate was similar for all groups, whereas in Study 2, the alcohol group reported more reversals than the control group, although this was true only for the biased versions of the Face‐Vase illusion. Conclusions: The effect of alcohol on reversal rate is observed only during intentional reversals of semantically meaningful stimuli and only when the stimulus is biased. Copyright © 2013 John Wiley & Sons, Ltd.